2023
DOI: 10.1021/acsenergylett.3c01330
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Stability of Perovskite Solar Cells through an Iodine Confining Strategy

Hui Yang,
Xiaodong Li,
Xuemin Guo
et al.

Abstract: One big challenge limiting the stability of perovskite solar cells (PSCs) is that iodine species produced in perovskite tend to diffuse and escape from PSCs, accelerating perovskite decomposition and destroying other functional layers as well. Motivated by the idea of iodine confinement in lithium–iodine batteries, here an iodine confining strategy is proposed to fabricate stable PSCs by incorporating poly(2-vinylpyridine) (P2VP) into the perovskite film. P2VP can effectively bond with the iodine product from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Crucially, MPP tracking at elevated temperatures and illumination, yielded improved device stability when prepared with β-CD, retaining an impressive 88.2% PCE after 1000 h. Similarly, polyvinylpyrrolidone (PVP), a polymeric iodophor widely used as an antiseptic, has also gained recent attention through its ability to form a complex with and act as a reservoir for I 2 capture within perovskites. 196–201 Interestingly, conflicting reports have so far been provided as to the exact optimum application with Kang et al choosing to add the iodine-bound form (PVP-I) whereas Yang et al opted for poly(2-vinylpyridine) (P2VP) with no starting bound-iodine. 196,198 In the former approach, the PVP-I provided a reservoir to replace iodine, preventing irreversible loss and depletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, MPP tracking at elevated temperatures and illumination, yielded improved device stability when prepared with β-CD, retaining an impressive 88.2% PCE after 1000 h. Similarly, polyvinylpyrrolidone (PVP), a polymeric iodophor widely used as an antiseptic, has also gained recent attention through its ability to form a complex with and act as a reservoir for I 2 capture within perovskites. 196–201 Interestingly, conflicting reports have so far been provided as to the exact optimum application with Kang et al choosing to add the iodine-bound form (PVP-I) whereas Yang et al opted for poly(2-vinylpyridine) (P2VP) with no starting bound-iodine. 196,198 In the former approach, the PVP-I provided a reservoir to replace iodine, preventing irreversible loss and depletion.…”
Section: Discussionmentioning
confidence: 99%
“…196–201 Interestingly, conflicting reports have so far been provided as to the exact optimum application with Kang et al choosing to add the iodine-bound form (PVP-I) whereas Yang et al opted for poly(2-vinylpyridine) (P2VP) with no starting bound-iodine. 196,198 In the former approach, the PVP-I provided a reservoir to replace iodine, preventing irreversible loss and depletion. While early DFT studies have warned about the impact of irreversible iodine depletion from the ABX 3 , little research has been offered as to how stoichiometry may be replenished dynamically and sustainably; this being essential for device longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-iodide redox chemistry has gained significance in diverse electrochemical energy technologies, such as supercapacitors, batteries (specifically metal–iodine and iodine-based redox flow batteries), solar cells, and hydrogen production. This is attributed to its lower overpotential, high theoretical storage capacity, cost-effectiveness, and natural abundance of iodine. In supercapacitors, specifically, integrating redox active additives in the electrolyte has emerged as a prominent strategy to enhance their energy density. ,, Among the various redox additives investigated in earlier studies, iodide-based additives employing iodine-iodide redox chemistry have shown exceptional promise, boasting an incredibly high specific capacitance exceeding 1000 F g –1 . , …”
Section: Introductionmentioning
confidence: 99%